Effect of provider recommendation style on the length of adolescent vaccine discussions. Issue 6 (5th February 2021) - Fenton, Anny T.H.R.; Orefice, Chelsea; Eun, Terresa J.; Biancarelli, Dea; Hanchate, Amresh; Drainoni, Mari-Lynn; Perkins, Rebecca B.
Abstract: Objective: To determine whether providers' vaccine recommendation style affects length of the adolescent vaccine discussions. Methods: We analyzed vaccine discussions using audio-recordings of clinical encounters where adolescents were eligible for HPV vaccines ± meningococcal vaccines. We measured length of vaccine discussions, the provider's use of an "indicated" (vaccination due at visit) or "elective" (vaccination is optional) recommendation style, and vaccine receipt. Parent and child demographics, parental vaccination intentions, and parental satisfaction with vaccine discussion were collected from pre- and post-visit surveys. We used linear and logit regressions with random effects to estimate recommendation style's association with discussion length and with vaccine receipt, respectively. Results: We analyzed 106 vaccine discussions (82 HPV; 24 meningococcal) across 82 clinical encounters and 43 providers. Vaccine discussions were longer when providers presented vaccination as elective versus indicated (140 vs. 74 s; p-value < 0.001). Controlling for vaccine type, parental vaccination intent, and patient characteristics, an elective style was associated with 41 seconds longer vaccine discussion (p-value < 0.05). Providers used the indicated style more frequently with the meningococcal vaccine than with the HPV vaccine (96% vs. 72%; p-value < 0.05). Parents' odds of vaccinating were 9.3 times higher following an indicated versus an elective presentation (p-value < 0.05). Vaccine discussion length and presentation style were not associated with parental satisfaction. Conclusions: Our results suggest that using an indicated recommendation improves vaccine discussions' efficiency and effectiveness, but this style is used more often with meningococcal than HPV vaccines. Increasing providers' use of indicated styles for HPV vaccines has the potential to increase vaccination rates and save time during medical visits.